Optimizing Asphalt Mixture Performance with Modified Buton Asphalt and Recycled PET using the Response Surface Methodology - Lapian, Franky Edwin Paskalis; Tumpu, Miswar; Irianto, . (Engineering, Technology & Applied Science Research, 2025)
In order to enhance asphalt-concrete mixtures, additives are used to improve durability and resilience to repeated road loads. The present study uses plastic waste as an additive and aims to find the optimal parameters for blending asphalt with additives made from Plastic Bottle Waste (PET) using Response Surface Methodology (RSM). The RSM approach, guided by the Design-Expert 8.0.6 software (Stat-Ease, Inc., Minneapolis, MN, USA), involved the design and analysis of a series of 17 experiments, employing a three-factorial Box-Behnken Design. The experimental design incorporated three primary independent variables, with the first (X1) being the ratio of PET to Modified Buton Asphalt (MBA), and the dependent variable (Y) corresponded to the Marshall characteristic, which serves as a measure of the reaction output. The results indicate that the incorporation of PET-based additives significantly enhances the stability, flow, and void characteristics of the asphalt mixture. The optimal mixture was achieved at an X1 of 2.0%:6.25%, which resulted in an improvement of Marshall stability by 47.89% compared to conventional asphalt mixtures. Furthermore, the addition of PET improved asphalt resistance to deformation and fatigue cracking. Consequently, it is recommended that further investigation be conducted into the potential of PET-based additives for large-scale applications in road construction, with a focus on long-term performance and environmental impacts.